The competent court and the governing law of copyright by reviewing international documents - Fatemeh alsadat Iravan mohajeri; Morteza Nassiri; Mahmoud Sadeghi (Faṣlnāmah-i Pizhūhish-i Huqūq-i Khuṣūṣī, 2019)
In the past, the protection of copyright was minimal, and the infringement of the copyright was regarded only as a tort. Conflict of law issues were resolved solely by the territorial approach to intellectual property rights and in accordance with the principle of national treatment. With the advent of the Internet, the availability and use of copyright were uncontrollably accelerated and facilitated, and the possibility of using cross-border copyright as well as the entry of the foreign element caused the complexity of these claims.The ubiquitous infringment of copy right is the result of broadcasting information on the internet and indeed in world that there is no solution for it in existing documents because of its novelty.The two fundamental issues of the governing law and the competent court in this article are aimed at responding to the efficiency or ineffectiveness of the common conflict of law system by studying the provisions of the Berne Convention as the most important document, the Brussels Convention and the ALI and the CLIP principles (as non-binding principles), and it was concluded that The traditional  system of conflict of laws is not enough for this purpose and doesn’t respond the copyright lawsuits and  so we requires a special conflict of law  system.